2019
DOI: 10.1002/ctpp.201900065
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of cubic non‐linearity‐driven electrostatic structures in the presence of double spectral index distribution function

Abstract: In this article, modified Korteweg-de Vries equation (which involves cubic non-linearity) was derived to study non-linear ion acoustic waves in a plasma in which electrons follow the double spectral index distribution function. The double spectral index distribution successfully apes the distribution functions that have been frequently observed in space plasmas. The spectral index r moulds the distribution function at low energy and by increasing its value, flatness of the distribution enhances. The spectral i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The effect of the electron to positron temperature ratio has also been investigated, and we found that maximum amplitudes of compressive and rarefactive solitons increase with the decrease and increase in the temperature ratio, respectively, although the changes are not very large. We also numerically solved the Sagdeev potential (25) and obtained the solitons by following the conditions (26) and (27). Our numerical results showed that solitons can be obtained for subsonic and supersonic regimes in kappa-distributed plasmas.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The effect of the electron to positron temperature ratio has also been investigated, and we found that maximum amplitudes of compressive and rarefactive solitons increase with the decrease and increase in the temperature ratio, respectively, although the changes are not very large. We also numerically solved the Sagdeev potential (25) and obtained the solitons by following the conditions (26) and (27). Our numerical results showed that solitons can be obtained for subsonic and supersonic regimes in kappa-distributed plasmas.…”
Section: Discussionmentioning
confidence: 87%
“…where Φ m is the maximum value of potential. From the above Equation 26, Mach number M must fulfil the following condition to obtain a soliton solution from Equation (25).…”
Section: Arbitrary Amplitude Solitary Wavesmentioning
confidence: 99%
See 2 more Smart Citations
“…The generalized ( ) r q , distribution has recently been used to explain data in the Earth's magnetosphere [33,34], and its impact on wave propagation in plasmas has also been studied [35,36]. However, the ( ) r q , distribution function's generalized version is [37]…”
Section: Introductionmentioning
confidence: 99%